Performance analysis framework for structural battery composites in electric vehicles - Carlstedt, David; Asp, Leif E. (Composites. Part B, Engineering, 2020)
In this paper, a novel modelling framework to estimate system level performance of electric vehicles utilizing a structural battery composite material is presented. Electrical and mechanical properties are derived from material data of the constituents, device design and connection/layup schemes. Knowledge of the multifunctional, i.e. electrical and mechanical, performance of the structural battery composite allows for estimation of the electric vehicle drive range for any known drive cycle. The framework is used to evaluate effect on drive range from the introduction of structural batteries into existing electric vehicles (EVs). Comparative studies performed for Tesla model S and BMW i3 demonstrate a compelling vehicle weight saving potential with maintained drive range performance. Alternatively, if vehicle weight is to be maintained from the introduction of structural batteries the resulting drive range for lightweight EVs will be increased by 70%.